2012
DOI: 10.2503/jjshs1.81.117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naringin Radical Formed by Peroxidase on Chlorophyll Degradation during Storage of Citrus nagato-yuzukichi Fruit

Abstract: Free radical formation from flavonoids by peroxidase action and changes in flavonoid levels and peroxidase activity during storage were determined to clarify the involvement of naringin radical in chlorophyll (Chl) degradation in stored green Nagato-yuzukichi (Citrus nagato-yuzukichi hort. ex Y. Tanaka) fruit. Chl a was degraded by peroxidase-hydrogen peroxide system not in the presence of hesperidin but with naringin. However, radical formation of both naringin and hesperidin, which were the main flavonoids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Likewise, high activity of chlorophyll‐degrading peroxidase was detected from small green to white stages of strawberry which corresponded with the diminishing of chlorophyll content and the drop in chlorophyll‐degrading activity as it ripened (Martinez et al., 2001). This chlorophyll‐degrading peroxidase has been claimed to be engaged in in vitro chlorophyll degradation of horticultural crops by oxidized phenolics compounds with the presence of hydrogen peroxide and formation of a phenoxy radical which directly breaks down chlorophyll‐a into a colorless compound (Yamauchi, 2015; Yamauchi et al., 2012). The complete disappearance of the greenish color of chlorophyll occurs at the late stage of the chlorophyll breakdown pathway to commonly yield short‐lived colorless fluorescent catabolites (FCCs) intermediates, which are further isomerized to form stable nonfluorescent chlorophyll catabolites (NCCs) as end products as found in ripened apples and pears (Moser et al., 2009).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Likewise, high activity of chlorophyll‐degrading peroxidase was detected from small green to white stages of strawberry which corresponded with the diminishing of chlorophyll content and the drop in chlorophyll‐degrading activity as it ripened (Martinez et al., 2001). This chlorophyll‐degrading peroxidase has been claimed to be engaged in in vitro chlorophyll degradation of horticultural crops by oxidized phenolics compounds with the presence of hydrogen peroxide and formation of a phenoxy radical which directly breaks down chlorophyll‐a into a colorless compound (Yamauchi, 2015; Yamauchi et al., 2012). The complete disappearance of the greenish color of chlorophyll occurs at the late stage of the chlorophyll breakdown pathway to commonly yield short‐lived colorless fluorescent catabolites (FCCs) intermediates, which are further isomerized to form stable nonfluorescent chlorophyll catabolites (NCCs) as end products as found in ripened apples and pears (Moser et al., 2009).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Most of these compounds related to peroxidase-dependent Chl degradation are phenolic compounds having a hydroxyl group at p-position. Consequently, p-coumaric acid and the flavonoids apigenin and naringenin, especially the former, which is (Kato and Shimizu, 1985;Yamauchi and Watada, 1994;Yamauchi et al, 2004Yamauchi et al, , 2012. According to the inhibitory effects of Tiron, nitroblue tetrazolium, MnCl 2 , AsA, and n-propyl gallate on peroxidase-mediated Chl degradation, we demonstrated that a phenoxy radical and/or a superoxide anion radical (·O 2 − ) could be involved in Chl degradation.…”
Section: ) Involvement Of the Phenoxy Radical In Peroxidasemediated mentioning
confidence: 85%
“…The protein precipitated by 45-60% saturated ammonium sulfates hardly included Chlase activity and was suitable for PPH determination. PPH activity in broccoli florets treated with UV-B was repressed for the first 2 days of storage at 15°C but gradually increased with yellowing of control broccoli florets (Aiamla-or et al, 2012).…”
Section: ) Involvement Of the Phenoxy Radical In Peroxidasemediated mentioning
confidence: 90%
See 2 more Smart Citations